In Vitro Quantification of the Effects of IP6 and Other Small Polyanions on Immature HIV-1 Particle Assembly and Core Stability - Dostálková, Alžběta; Kaufman, Filip; Křížová, Ivana; Vokatá, Barbora; Ruml, Tomáš; Rumlová, Michaela (Journal of virology, 2020)
Proper assembly and disassembly of both immature and mature HIV-1 hexameric lattices are critical for successful viral replication. These processes are facilitated by several host-cell factors, one of which is myo-inositol hexaphosphate (IP6). IP6 participates in the proper assembly of Gag into immature hexameric lattices and is incorporated into HIV-1 particles. Following maturation, IP6 is also likely to participate in stabilizing capsid protein-mediated mature hexameric lattices. Although a structural-functional analysis of the importance of IP6 in the HIV-1 life cycle has been reported, the effect of IP6 has not yet been quantified. Using two in vitro methods, we quantified the effect of IP6 on the assembly of immature-like HIV-1 particles, as well as its stabilizing effect during disassembly of mature-like particles connected with uncoating. We analyzed a broad range of molar ratios of protein hexamers to IP6 molecules during assembly and disassembly. The specificity of the IP6-facilitated effect on HIV-1 particle assembly and stability was verified by K290A, K359A, and R18A mutants. In addition to IP6, we also tested other polyanions as potential assembly cofactors or stabilizers of viral particles.IMPORTANCE Various host cell factors facilitate critical steps in the HIV-1 replication cycle. One of these factors is myo-inositol hexaphosphate (IP6), which contributes to assembly of HIV-1 immature particles and helps maintain the well-balanced metastability of the core in the mature infectious virus. Using a combination of two in vitro methods to monitor assembly of immature HIV-1 particles and disassembly of the mature core-like structure, we quantified the contribution of IP6 and other small polyanion molecules to these essential steps in the viral life cycle. Our data showed that IP6 contributes substantially to increasing the assembly of HIV-1 immature particles. Additionally, our analysis confirmed the important role of two HIV-1 capsid lysine residues involved in interactions with IP6. We found that myo-inositol hexasulphate also stabilized the HIV-1 mature particles in a concentration-dependent manner, indicating that targeting this group of small molecules may have therapeutic potential.
Keywords: polyelektrolyty; Mutation, Missense; polyanion; HIV-1; missense mutace; Structure-Activity Relationship; IP6; Polymers; Amino Acid Substitution; vztahy mezi strukturou a aktivitou; capsid; polymery; mature; substituce aminokyselin; assembly; Polyelectrolytes; genové produkty gag - virus lidské imunodeficience; gag Gene Products, Human Immunodeficiency Virus; Virus Assembly; immature; sestavení viru